A comparison of gas chromatography coupled to tandem quadrupole mass spectrometry and high-resolution sector mass spectrometry for sensitive determination of polycyclic aromatic hydrocarbons (PAHs) in cereal products. (15th April 2017) - Rozentale, Irina; Zacs, Dzintars; Perkons, Ingus; Bartkevics, Vadims
Highlights: Sensitive and accurate analysis for very low concentrations of PAHs was developed. GC-MS/MS and GC-HRMS methods were compared. Methods LODs varied between 0.002 μg kg −1 and 0.006 μg kg −1 . Methods demonstrated appropriate performance in PAHs analysis even at low contamination levels. Abstract: Due to the high consumption level, cereals represent one of the major sources of human exposure to PAHs. Taking into account the low maximum permitted level (ML) established in the European Union (EU) for the sum of four priority PAHs (PAH4) in processed cereal-based foods, sensitive and selective analysis for very low concentrations of these carcinogenic compounds was developed and compared by applying two different analytical techniques. Elaborated methods demonstrated appropriate performance in PAHs analysis even at low contamination levels. Limits of detection (LOD) for the PAH4 varied between 0.002 μg kg −1 and 0.006 μg kg −1, recoveries were in the range of 92–103% for GC-MS/MS and 108–117% for GC-HRMS. Elaborated methods were applied for the analysis of 35 Latvian cereals and bread samples. The concentrations of PAH4 were in a range of 0.22–1.62 μg kg −1 with 14% of samples exceeding the current EU maximum permitted levels.